Time estimation and time perceiving in patients receiving intravenous anaesthesia for endoscopic procedures - Płotek, Włodzimierz; Sobol-Kwapinska, Małgorzata; Cybulski, Marcin; Kluzik, Anna; Grześkowiak, Małgorzata; Drobnik, Leon (Journal of Medical Science, 2015)
Introduction. The basic goals of the study were to analyze how patients receiving intravenous anaesthesia for endoscopy produce one-minute time intervals after anaesthesia, and to characterize the relationship between attitude towards time and the production of one-minute intervals. Material and methods. Twenty four intravenously anesthetized patients constituted the Anaesthesia Group and 25 nonanesthetized patients formed the Control Group. The Mini-Mental State Examination and the Sense of Coherence Meaningfulness Subscale were used to recognize the problem of dementia and depression, the Time Metaphors Questionnaire was used for the assessment attitudes toward time. Time production of one-minute was measured three times in each of four sessions. Results. The tested participants of both groups shortened the one-minute intervals. Duration of anaesthesia did not affect the time production. Perceiving time as empty and meaningless was related with misestimating time after colonoscopy. Conclusions. Time interpretation by using metaphors and time production are related with each other.